2011
DOI: 10.1016/j.compositesa.2011.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Effect of various chemical treatments on the fibre structure and tensile properties of industrial hemp fibres

Abstract: Industrial hemp fibres were treated with sodium hydroxide, acetic anhydride, maleic anhydride and silane to investigate the influence of treatment on the fibre structure and tensile properties. It was observed that the average tensile strength of sodium hydroxide treated fibres slightly increased compared with that of untreated fibres, which was believed to be as a result of increased cellulose crystallinity. The average tensile strength of acetic anhydride, maleic anhydride, silane and combined sodium hydroxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
194
2
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 325 publications
(210 citation statements)
references
References 30 publications
13
194
2
1
Order By: Relevance
“…Sawpan et al [28] also observed the kinks in the structure Adhesive covering the fibre (the pulled-out region)…”
Section: Introductionmentioning
confidence: 97%
“…Sawpan et al [28] also observed the kinks in the structure Adhesive covering the fibre (the pulled-out region)…”
Section: Introductionmentioning
confidence: 97%
“…The size of fibers was sorted by sieve shaker using 30 (large fiber (LF)), 60 (middle fiber (MF)), and 80 (small fiber (SF)) mesh, respectively. Fibers were then cleaned by soaking in hot water at a temperature of 50°C for 30 min and then dried in the oven at 80°C for 48 h. 22 …”
Section: Preparation Of the Hwc Fibermentioning
confidence: 99%
“…After the lignin has been removed by alkali, hemicellulose depolymerization occurs; the reducing end-group of the hemicellulose chain is oxidized (Keller et al 2001;Sinha and Rout 2008;Sawpan et al 2011;Sharma et al 2011). Cellulose is easily hydrolyzed by acid and easily oxidized.…”
Section: Peer-reviewed Articlementioning
confidence: 99%
“…Wetting allows the hemp fiber to swell and become loose, which improves the penetration of scouring agents. Under alkaline conditions, lignin reacts with alkali, and the ether bonds present in the compounds of α-phenyl ether, α-alkyl ether, β-aryl ether, and aryl ether linked with lignin would be attacked by nucleophile of OH -and broken, In addition, the reaction degrades and dissolves large molecules such as lignin.After the lignin has been removed by alkali, hemicellulose depolymerization occurs; the reducing end-group of the hemicellulose chain is oxidized (Keller et al 2001;Sinha and Rout 2008;Sawpan et al 2011;Sharma et al 2011). Cellulose is easily hydrolyzed by acid and easily oxidized.…”
mentioning
confidence: 99%